SOSIALISASI DAN PENDAMPINGAN PEMBUATAN SABUN CUCI TANGAN (CAIR) DARI LIMBAH MINYAK GORENG BEKAS BAGI IBU RUMAH TANGGA KELURAHAN JAYAMUKTI - Nisa Nurhidayanti; Fitri Rezeki; Erina Rulianti; Andini Putri Riandani; Retno Fitri Astuti (Jurnal Pengabdian Masyarakat (Jupemas), 2023)
Cooking oil that is used repeatedly can be harmful to human health, but if it is disposed of carelessly it can pollute the environment, such as contamination of sewers, clean water and ground water and so on. So it is necessary to process used cooking oil into useful products. This service activity aims to equip residents with the ability to process cooking oil waste which was previously waste that polluted the environment. This service activity includes five stages, namely planning, coordination, socialization, assistance in making laundry soap products and evaluation and follow-up. The results of this community service activity are liquid laundry soap products that can be used to wash hands or wash dishes. The evaluation results of PkM activities were obtained from the input of several PkM participants, so it is necessary to try out the production of liquid soap on a larger scale, such as using used cooking oil waste in the neighborhood community or community association, so that it can be used as a productive activity for housewives who want to develop a business. or produce liquid soap for use independently. Liquid soap products that are used are safer because they do not add various kinds of chemicals.